2014
DOI: 10.1016/j.jbiomech.2013.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Altered biomechanical strategies and medio-lateral control of the knee represent incomplete recovery of individuals with injury during single leg hop

Abstract: Anterior cruciate ligament (ACL) injury can result in failure to return to pre-injury activity levels and future osteoarthritis predisposition. Single leg hop is used in late rehabilitation to evaluate recovery and inform treatment but biomechanical understanding of this activity is insufficient.This study investigated single leg hop for distance aiming to evaluate if ACL patients had recovered: (1) landing strategies and (2) medio-lateral knee control. We hypothesized that patients with reconstructive surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…The knee axes were aligned using the anatomical calibration trial. In some trials the trunk and hips flexed as such that the markers on the left and right anterior superior iliac crests (LASI and RASI) were occluded; these gaps were filled using the data of the LILC and RILC markers in a custom written programme in Vicon BodyBuilder for T=1/f) was used so that a larger value agreed with a more fluent movement [13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The knee axes were aligned using the anatomical calibration trial. In some trials the trunk and hips flexed as such that the markers on the left and right anterior superior iliac crests (LASI and RASI) were occluded; these gaps were filled using the data of the LILC and RILC markers in a custom written programme in Vicon BodyBuilder for T=1/f) was used so that a larger value agreed with a more fluent movement [13].…”
Section: Methodsmentioning
confidence: 99%
“…For example, poor knee control in the frontal plane during hopping has been associated with increased risk of anterior cruciate ligament (ACL) injury [8] and increased medial knee loading in the frontal plane during walking has been associated with development of osteoarthritis [9]. Therefore, knee movement assessment in the frontal plane is routine clinical practice [10] and improvement of knee control in the frontal plane is an important objective during functional exercises which will focus on neutral alignment of the knee [8,[10][11], movement fluency [12][13][14] and displacement variability [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The other eleven studies investigated biomechanical variables in the context of stability and postural control [37][38][39][40], gait [41], vision [42], limb asymmetry [43], walk and jog patterns [44], gender differences [45], as well as neuromuscular aspects [46]. Landing strategies and medio-lateral control of the ACLD and ACLR patients were also investigated by Roos et al [47] and found that these groups had not fully recovered.…”
Section: Level 2 Evidencementioning
confidence: 99%